The Juridical Implications of the Status of Children Out of Wedlock after the Stipulation of the Constitutional Court Decision Number: 46/PUUVIII/2010 - Paburru, Faely (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to: 1. To find out the juridical implications of the position of illegitimate children after the stipulation of the Constitutional Court decision No: 46/PUUVIII/2010. 2. To find out the distribution of inheritance rights for children out of wedlock if there is a blood relationship with children out of wedlock. 3. Deed of inheritance rights issued by a notary. The approach in this research is the empirical juridical approach. Empirical juridical research is a problem approach regarding matters that are juridical in nature and the existing facts regarding matters that are juridical in nature. Empirical legal research or sociological research is legal research that uses primary data. The results of this study: 1. Juridical implications of the status of children outside of marriage after the stipulation of the Constitutional Court Decision Number: 46/PUUVIII/2010. The implications that arise from the presence of the Constitutional Court Decision Number 46/PUU-VIII/2010, children out of wedlock in Islamic law still only have the right to have family relations with their mother and family from their mother's side. As stated in Article 100 of the Compilation of Islamic Law (KHI) which reads: